A Study of investor behavior in purchasing financial assets - Ruhani Ali; Jiang, Haibing (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study investigated whether the process of purchasing financial assets follows a rational decision-making process using Engel-Blackwell-Miniard (EBM) model. The method of investigation was a questionnaire survey of Malaysian individual investors. The sample consisted of 223 responses collected through convenience sampling and online survey. The data was analyzed using factor analysis, reliability analysis, path analysis, and multivariate analysis of variance. The results show that investors' decision-making process of purchasing financial assets is in line with a rational decision-making process in EBM Model. However, the tendency for irrational investment behaviors also exists at the same time. The findings imply that irrational investment behaviors may still occur even though the decision-making process is rational. We also found significant differences in the tendencies for herding, disposition effect and over-confidence based on gender and age.